Treponema pallidum, the syphilis spirochete: making a living as a stealth pathogen - Radolf, Justin D; Deka, Ranjit K; Anand, Arvind; Šmajs, David; Norgard, Michael V; Yang, X Frank (Nature reviews. Microbiology, 2016)
The past two decades have seen a worldwide resurgence in infections caused by Treponema pallidum subsp. pallidum, the syphilis spirochete. The well-recognized capacity of the syphilis spirochete for early dissemination and immune evasion has earned it the designation 'the stealth pathogen'. Despite the many hurdles to studying syphilis pathogenesis, most notably the inability to culture and to genetically manipulate T. pallidum, in recent years, considerable progress has been made in elucidating the structural, physiological, and regulatory facets of T. pallidum pathogenicity. In this Review, we integrate this eclectic body of information to garner fresh insights into the highly successful parasitic lifestyles of the syphilis spirochete and related pathogenic treponemes.
Keywords: Immune Evasion; bakteriální proteiny; syfilis; Syphilis; toll-like receptor 2; Toll-Like Receptor 2; Treponema pallidum; lidé; Bacterial Proteins; Genomics; Bacterial Outer Membrane Proteins; Humans; sekvenční seřazení; proteiny vnější bakteriální membrány; imunitní únik; Sequence Alignment; genomika